IMF conditionality – a better way - J. SPRAOS (PSL Quarterly Review, 2013)
The article looks at IMF conditions for upper credit tranche stand-by arrangements. The IMF must face the criticism that its recent actions have transgressed on private banks' territory because of banks' errors in lending to third world countries - a matter that could have been left to free market forces. Conditions for IMF aid should focus not on policy instruments but on policy targets, such as growth, employment, inflation and, ultimately, restoration of countries' balance of payments positions. Conditions for IMF help should be centred squarely on the balance of payments of aid-seeking countries if a backwards trend is to be avoided.